ANALISIS EKONOMI RUMAH TANGGA PETANI KARET EKS UPP TCSDP DI DEBA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Putri Wulandari; Shorea Khaswarina; Suardi Tarumun (Indonesian Journal of Agricultural Economics, 2016)
This research is aimed to analyze the household economics of ex-rubber farmers of UPP TSCDP. In order to answer the purpose of research, descriptive analysis and econometric approach with a model of simultaneous equations using Two Stage Least Square (2SLS) were used. The results of this research are household rubber farmers allocated more times working in rubber farming which is 1268.8 hours/year (67.34%) and 622.3 hours/year (32.66%) was allocated to work outside rubber farming. The income of rubber farmers household comes more from rubber farming which is Rp.18.684.884,0/year instead of outside the rubber farming worth Rp.11.041.624,0 / year. The expenditure of rubber farmers more on non-food consumption which is Rp.11.685.008/year instead of food consumption Rp.10.640.756/year. In the production block, there are not factors that responsive to economic decisions of households rubber farmers, but the greatest impact is the number of productive rubber trees. However, the factors that responsive for allocated of working time is responsive farmers work experienced and age of the farmer. On the revenue block, the educational factors are responsive to economic decisions of households rubber farmers. While the expenditure, the factor that responsive isthe total income of farmers, the wife of education, the number of school children rubber farmer households and non-food consumption.